Quantitative evaluation of interaction effect between plate-parallel airflow and system of vortexes - Кулик, Н. С.; Гвоздецкий, И. И.; Кинащук, И. Ф.; Кудряшов, Б. Я. (Proceedings of National Aviation University (archive), 1999)
Presented is the description of experimental test-bench used for explanation and quantitative analysis of interaction effect between plate-parallel airflow and system of vortexes. Special attention is given to construction of full-scale modelling unit, parameters of mainstream gas detection and controlling system, vortex creating channels controlling system